The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.resourpol.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of outliers and oil price shocks on volatility of metal prices

Abstract: SummaryThis study investigates the price volatility of metals, using the GARCH and GJR models. First we examine the persistence of volatility and the leverage effect across metal markets taking into account the presence of outliers, and second we estimate the effects of oil price shocks on the price volatility of metals, allowing for the asymmetric responses. We use daily spot prices for the selected metals, including aluminum, copper, lead, nickel, tin, zinc, gold, silver, palladium and platinum.The main find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 51 publications
(36 reference statements)
0
31
0
Order By: Relevance
“…From the demand perspective, accompanying the advent of accelerated industrialization and urbanization, explosive demand growth in emerging countries like China has drastically boosted price for copper, which is used as a pivotal input in manufacturing (Jerrett and Cuddington, 2008;Irandoust, 2017). Nevertheless, in the context of the commodity financialization, the key role of excessive speculation in pushing price above the level justified by market fundamentals has been highlighted in the copper market (Behmiri and Manera, 2015). In addition, the U.S. dollar has been a contributing factor to additional volatility since the international copper price is typically denominated in it (Buncic and Moretto, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the demand perspective, accompanying the advent of accelerated industrialization and urbanization, explosive demand growth in emerging countries like China has drastically boosted price for copper, which is used as a pivotal input in manufacturing (Jerrett and Cuddington, 2008;Irandoust, 2017). Nevertheless, in the context of the commodity financialization, the key role of excessive speculation in pushing price above the level justified by market fundamentals has been highlighted in the copper market (Behmiri and Manera, 2015). In addition, the U.S. dollar has been a contributing factor to additional volatility since the international copper price is typically denominated in it (Buncic and Moretto, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A second bulk of the literature addresses the co-movement and volatility spillover between energy and metal markets (Aguilera and Radetzki 2017;Behmiri and Manera, 2015;Bildirici and Turkmen. 2015;Choi and Hammoudeh, 2010;Ewing and Malik, 2013;Hammoudeh and Yuan, 2008;Ji et al, 2018b.…”
Section: Fowowe (2016) Uses Cointegration Tests With Structural Breakmentioning
confidence: 99%
“…For example, Choi and Hammoudeh (2010) investigate the volatility transmission between oil and industrial commodities using a regimeswitching model, while Bildirici and Turkmen (2015) analyse the cointegration and causality relationship among oil and precious metals using a nonlinear ARDL cointegration framework and nonlinear causality tests. Whereas Aguilera and Radetzki (2017) investigate the synchronisation of oil and gold prices, Behmiri and Manera (2015) underline the role of oil price shocks to explain volatility in metal prices.…”
Section: Fowowe (2016) Uses Cointegration Tests With Structural Breakmentioning
confidence: 99%
“…Early studies on volatility modeling and forecasting in the metal market primarily focused on generalized autoregressive conditional heteroskedasticity (GARCH)type models (Behmiri & Manera, 2015;Bentes, 2015;Hammoudeh, Malik, & McAleer, 2011;Hammoudeh & Yuan, 2008;Kristjanpoller & Hernández, 2017;Kristjanpoller & Minutolo, 2015;McKenzie, Mitchell, Brooks, & Faff, 2001). More recent literature suggests that high-frequency data can significantly improve the prediction accuracy of future volatility (Gong, He, Li, & Zhu, 2014;Wang & Wang, 2016;Wen, Gong, & Cai, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Watkins and McAleer (2004) found that only 45 referred to publications concentrating on metal's price volatility between 1980 and 2002 and none of them utilized intraday data. The literature on metals concentrates on volatility properties (Hammoudeh & Yuan, 2008;Todorova, 2015;Watkins & McAleer, 2008), spillover effects and information flows in different markets (Aruga & Managi, 2011;Cochran, Mansur, & Odusami, 2012;Hammoudeh, Yuan, McAleer, & Thompson, 2010;Lien & Yang, 2009;Sensoy, 2013;Xu & Fung, 2005), and the impact of news sentiment, investor sentiment, speculation, outliers and oil price shocks on the volatility of metal prices (Balcilar, Bonato, Demirer, & Gupta, 2017;Behmiri & Manera, 2015;Bosch & Pradkhan, 2015;Fassas, 2012;Smales, 2015).…”
Section: Introductionmentioning
confidence: 99%